Analisa Nilai Kekasaran Permukaan Material Baja Aisi 1040 Pada Proses Pemesinan CNC BUBUT Menggunakan Metode Taguchi - Yongki, Yongki; Subhan, Muhammad; Riezky Pratiwi, Indah; Ary Wahyudie, Ilham (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The factor that must be considered in the machining process is the level of surface roughness of the material being processed. Computer Numerical Control (CNC) machines help in producing large quantities of products without resetting the computer program. The process variables used in this study were feed speed with variations in levels of 140 mm/minute and 180 mm/minute, depth of ingestion with variations in levels of 0.5 mm and 0.7 mm, and feeding motion with variations in levels of 0.25 mm/put and 0.5mm/put. The analysis was carried out using the taguchi calculation method. The results of research data analysis that has been carried out on the surface roughness value of AISI 1040 steel can be determined that setting the variable settings in the CNC lathe machining process to produce the lowest surface roughness value on AISI 1040 steel material can be obtained by a combination of speed variables feed 180 m/minute (level 2), depth of feed 0.7 mm (level 2) and feed 0.25 mm/put (level 1) with a contribution value of . Where the contribution of feed motion makes the greatest contribution to the surface roughness response when compared to other factors, namely 31.3764%. The second contribution that influences the response to surface roughness is feed speed, which is 16.8977%. depth of ingestion is 5.1126%.